CULTIVATION OF VEGETABLE ROOT CROPS OF BRASSICACEAE FAMILY IN INDOOR PLANTING - Yu. K. Zemskova; A. V. Savchenko (Овощи России)
The results of winter and spring sowing times of vegetable root crops of Brassicaceae family in protected area are presented. Five varieties and three hybrids of daikon, seven varieties of radish, and five varieties of turnip were studied. The minimal and maximal weight of roots for each sowing time was revealed. The average weight of products over three years of research was calculated.